Systematic review on the Minnesota Multiphasic Personality Inventory (MMPI) - Zambrano-Guerrero, Christian Alexander; Caicedo Padilla, Diego Andrés; Matabanchoy Tulcán, Sonia Maritza (Universidad y Salud, 2015)
This article sought to determine the applicability of the test of personality Minnesota multiphasic personality inventory (MMPI) through the last 25 years, through the methodology of systematic review of the literature in 41 studies in free access database such as: Organization of the United Nations for food and culture, MedlinePlus, Open Journal Systems , Dialnet, Scielo, Wiley Open Access, UNESCO, Latindex, Ebsco Host and Redalyc; which allowed to collect information about the instrument and its application in different contexts and moments from 1990 to 2015. It is concluded that most of the investigations have shown the validity and reliability of the MMPI as well as the need to continue studies in relation to the implementation, validation and systematization of the instrument.